Fatigue Performance of 6063-T66 Aluminum Alloy under Combined Cyclic Loading of Parent and Welded Specimens - Kopas, Peter; Saga, Milan; Uhricik, Milan (Communications - Scientific letters of the University of Zilina, 2012)
The article deals with the determining of fatigue lifetime of structural materials during multiaxial cyclic loading. The aim of this investigation is to evaluate the influence on fatigue behavior of the welded aluminum alloy EN AW 6063-T66. Experimental device was designed for combined bending – torque loading. The experimental part was focused on the modeling of combined biaxial loading and determining the number of cycles to fracture in the region of low-cycle fatigue. In-phase loading can be treated fairly well using the conventional hypotheses (von Mises or Tresca) on basis of nominal, structural or local strains or stresses. Based on the experimental results the fatigue design curves are compared to fatigue data from base metal and weldments.